Keanekargaman dan Tingkat Serangan Hama Penggerek Batang Padi Sawah pada Varietas Inpari 36 dan Varietas Solok Putih di Kota Sungai Penuh - Sinta Fitria; Yuni Ratna; Mohammad Zuhdi (Jurnal Media Pertanian, 2026)
The study was conducted to analyze the diversity and level of rice stem borer (PBP) attacks on the Inpari 36 and Solok Putih varieties in Sungai Penuh City. The study was conducted using a survey method from April to September 2024 in eight sub-districts in Sungai Penuh City. In each sub-district there are two observation plots, namely the Inpari 36 Variety plot and the Solok Putih Variety plot, each 10 x 10 m2. Observations of attack intensity were made 6 times at plant age 28 HST, 42 HST, 56 HST, 70 HST, 84 HST and 98 HST. Data on types, pest populations and attack intensity obtained were tabulated and analyzed descriptively and statistically. The results of the calculation of the Shannon-Wiener diversity index (H ') and evenness index (E) for two rice varieties, namely Inpari 36 and Solok Putih, obtained H 'values ranging from 0.62-0.69 with E values between 0.90-1.00. The value indicates that the level of diversity of rice stem borer species in all observation locations is low (H’